2020
DOI: 10.15406/ppij.2020.08.00289
|View full text |Cite
|
Sign up to set email alerts
|

A review of Titanium, Vanadium and Chromium transition metal Schiff base complexes with biological and catalytic activities

Abstract: Schiff bases are compounds obtained from the condensation reaction of a primary amine and aldehyde or ketone. They can be coordinated with metals especially the transition metals to form Schiff base complexes. The objective of this work is to review the synthesis, biological as well as catalytic activities of both Schiff base ligands and their transition metal complexes of titanium, vanadium as well as chromium. The methodology used for looking for the references were through the internet. Biological activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Interest in the coordination complexes of vanadium is primarily due to their variety of roles in biological processes such as nitrogen fixation, haloperoxidation, phosphorylation, insulin mimicking, anti-microbial and anti-fungal activities, and for their possible use as efficient catalysts in various organic reactions (Noblı ´a et al, 2004;Plass et al, 2007;Zabin & Abdelbaset, 2016;Tsave et al, 2016;Tanabe & Nishibayashi, 2019;Assey & Mgohamwende, 2020). Oxovanadium(V) (VO 3+ ) and dioxovanadium(V) (VO 2 + ) catalyzed reactions include C-C bond formation, hydrogenation, dehydrogenation, sulfide oxidation, C-C/C-O bond cleavage, alcohol/aldehyde/ketone oxidation, deoxydehydration (Langeslay et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Interest in the coordination complexes of vanadium is primarily due to their variety of roles in biological processes such as nitrogen fixation, haloperoxidation, phosphorylation, insulin mimicking, anti-microbial and anti-fungal activities, and for their possible use as efficient catalysts in various organic reactions (Noblı ´a et al, 2004;Plass et al, 2007;Zabin & Abdelbaset, 2016;Tsave et al, 2016;Tanabe & Nishibayashi, 2019;Assey & Mgohamwende, 2020). Oxovanadium(V) (VO 3+ ) and dioxovanadium(V) (VO 2 + ) catalyzed reactions include C-C bond formation, hydrogenation, dehydrogenation, sulfide oxidation, C-C/C-O bond cleavage, alcohol/aldehyde/ketone oxidation, deoxydehydration (Langeslay et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Recent studies have indicated that complexes of metals such as chromium, cobalt, copper, vanadium, manganese, and zinc have huge potential as antimicrobial, anticancer, antioxidant, and antidiabetic properties ( Senthil Raja et al, 2012 ; Al-Hazmi et al, 2020 ). In this regard, Vanadium and chromium play crucial roles and are known for their significant bioactivities like antimicrobial, anticancer, and antiviral ( Crans et al, 2018 ; 2019 ; Selman et al, 2018 ; Assey and Mgohamwende, 2020 ; Suma et al, 2020 ). Vanadium can exist in many oxidation states; therefore, vanadium complexes are attractive to researchers for their promising biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium can exist in many oxidation states; therefore, vanadium complexes are attractive to researchers for their promising biological activities. Several reports are on synthesizing vanadium complexes with different ligands to determine their magnetic, antidiabetic, antioxidant, and catalytic properties ( Crans et al, 2019 ; Assey and Mgohamwende, 2020 ). However, vanadium and chromium-based complexes’ antibacterial and anticancer activity is rarely studied ( Singh and Gupta, 2008 ; Al-Hazmi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionalization of hydrazine improves the efficiency of the materials and may create new properties in it. Among various functionalizations, one with Schiff base is trending due to the diverse properties of Schiff base including antibacterial [13,14], antifungal [15][16][17], antioxidant [18][19][20], antiviral [21], antitumor [22], anti-inflammatory [23,24], biomimics [25], luminescence [26] and catalytic activity [27][28][29]. A brief literature survey shows that Biswas et al has successfully designed a Schiff base functionalized with hydrazine and employed it for the synthesis of nanoaggregates that showed blue emission properties [30].…”
Section: Introductionmentioning
confidence: 99%